Highlights of the interim review meeting of the joint innovative project on in-service primary teacher education held on 22-29 January 1981, Bangkok, Thailand. (Education quarterly.)
After the initial planning meeting, the participating countries developed their respective research designs and tools and started work on national studies. The interim review was held to review the progress of the work, revise plans of study including the research design and tools, and discuss the future source of action to be taken in the project.